2017
DOI: 10.1161/strokeaha.117.019258
|View full text |Cite
|
Sign up to set email alerts
|

Structural Integrity of Normal Appearing White Matter and Sex-Specific Outcomes After Acute Ischemic Stroke

Abstract: Background and Purpose Women have worse post-stroke outcomes than men. We evaluated sex-specific clinical and neuroimaging characteristics of white matter in association with functional recovery after acute ischemic stroke (AIS). Methods We performed a retrospective analysis of AIS patients with admission brain MRI and 3 to 6 month modified Rankin scale score (mRS). White matter hyperintensity (WMH) and acute infarct volume were quantified on fluid attenuated inversion recovery (FLAIR) and diffusion-tensor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Our finding of sex-specific differences in NAWM K 2 coefficient, as a putative measure of BBB dysfunction, is of clinical interest. We have previously reported an association between NAWM structural integrity (fractional anisotropy) and sex-specific functional outcomes 11. Together, these observations offer some insight into the potential factors contributing to the disparity in stroke outcomes between sexes as they suggest that sex-specific differences in NAWM microvascular integrity predispose to worse outcomes in women.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our finding of sex-specific differences in NAWM K 2 coefficient, as a putative measure of BBB dysfunction, is of clinical interest. We have previously reported an association between NAWM structural integrity (fractional anisotropy) and sex-specific functional outcomes 11. Together, these observations offer some insight into the potential factors contributing to the disparity in stroke outcomes between sexes as they suggest that sex-specific differences in NAWM microvascular integrity predispose to worse outcomes in women.…”
Section: Discussionmentioning
confidence: 65%
“…WMH lesions in the hemisphere contralateral to the acute infarct were outlined in a semi-automated manner using MRIcro software as described previously 11 19. All images were analysed by trained research staff that were blinded to all outcome data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences were seen for IS as females had higher incidence and longer life expectancy but worse functional outcomes [3,4], which might be due to different risk factors [5,6,7], anatomic structural Willis incompletion or white integrity [8,9], biologically inherent sex chromosome complemented with gonadal hormones [10,11,12], socialized reasons of in-hospital care [6,13], and therefore, pathology and treatment [14,15]. However, animal-based research has observed decreased infarct size and improved outcomes in female compared to males [16].…”
Section: Introductionmentioning
confidence: 99%
“…While age-specific stroke rates are higher in men, women have relatively more stroke events because of their longer life expectancy [ 1 ]. In addition women are less likely to show excellent recovery [ 2 ]. There is a time-of-day dependent variation in the vulnerability to ischemia and in the occurrence of ischemic events [ 3 , 4 ], and shift work has been shown to be a risk factor for cardiovascular diseases in women [ 5 ].…”
Section: Introductionmentioning
confidence: 99%